INTEGRATING LOCAL CULTURE IN ENGLISH LANGUAGE TEACHING TO INCREASE LEARNERS’ MOTIVATION TO SPEAK ENGLISH - Weni Ramadiani; Anni Holila Pulungan (Universitas Negeri Medan, 2022)
This research aim at exploring how local culture integrated in English languageteaching to increase learners’ motivation to speak English. This research wascarried out of eighth grade students’ at SMPN 3 Perbaungan. This research wasconducted by using descriptive qualitative data. The data of this research werecollected by using observation, interview and audio recording. the samples wereselected purposively based on their cultural backgrounds. The result revealed thatby integrating local culture in learning English was easier for the learners. Thelearners had willingness to speak English since most of they were familiar withcultural input.